Enchantment : the art of changing hearts, minds, and actions - Kawasaki, Guy, 1954- (New York : Portfolio/Penguin, 2011)
Guy Kawasaki's acclaimed books have established him as the entrepreneur's entrepreneur. Now he turns to the mystery of influence, and offers a new take on this key force that drives any successful business or personal interaction. This book's fundamental message is that in any transaction the goal is not to get your own way, but to bring about a voluntary, enduring, and delightful change of heart in other people, by working with and through them and enlisting their own goals and desires. It's enchantment that enables us to maneuver through difficult decisions, break people's entrenched habits, defy the wisdom of crowds, and get colleagues to work for long-term goals. Kawasaki's advice includes: how to achieve rapport, credibility, and trust; how to help people enchant themselves; how to overcome resistance; how to enchant your employees--and your boss; and how to resist enchantment.--From publisher description.
Introduction -- Why enchantment? -- How to achieve likability -- How to achieve trustworthiness -- How to prepare -- How to launch -- How to overcome resistance -- How to make enchantment endure -- How to use push technology -- How to use pull technology -- How to enchant your employees -- How to enchant your boss -- How to resist enchantment -- Conclusion.
Includes bibliographical references and index.
Keywords: Persuasion (Psychology) in organizations; Persuasion (Psychology); Influence (Psychology); Marketing -- Psychological aspects; Management -- Psychological aspects